The (army) hero with a thousand faces: A discourse-mythological approach to theorising archetypal blending in contemporary advertising. (March 2023) - Kelsey, Darren; Yannopoulou, Natalia; Whittle, Andrea; Heath, Teresa; Golossenko, Artyom; Soares, Ana Maria
This manuscript theorises the use of heroism in marketing by analysing selected representations of the army hero in contemporary advertising. Adopting the discourse-mythological approach to analyse Jungian archetypes, we focus on three US advertising campaigns that depict the army hero. Our analysis reveals that representations of the army hero combine traits, symbols, and images of the Magician, Warrior and King archetypes. 'Archetypal blending' is theorised in order to understand the mythological complexities of modern heroism, which expands the individually centred Hero's Journey through references to a collective journey and collective responsibility. This study advances theoretical insights into how advertising blends narratives of heroism and other mythical archetypes to remain meaningful to multiple audiences - balancing the reproduction of conventional views of military heroism with representations that reflect changing societal values.